Clinical patterns and management of primary mucosal melanoma: a single centre experience. Issue 11 (1st February 2018) - Ng, Yvonne Y. R.; Tan, Grace H. C.; Quek, Richard H. H.; Farid, Mohamad B. H. R.; Soo, Khee Chee; Teo, Melissa C. C.
Abstract : Background: Primary mucosal melanomas (MM) are rare neoplasms arising from melanocytes in mucosal membranes. Delayed diagnosis and aggressive disease biology contribute to a poorer prognosis. The clinical patterns of MMs treated in a large tertiary centre, and the differences between MMs in the head and neck versus other anatomical sites are described. Methods: A retrospective review of 43 patients diagnosed with MM in the head and neck, urogenital, esophageal and anorectal sites from 1993 to 2015 was conducted. Results: Distribution of head and neck, urogenital and gastrointestinal MM were 42, 30 and 28% respectively. Disease extent was local in 44%, regional in 40% and distal in 12% at diagnosis. Head and neck MMs were more likely to be diagnosed at an earlier stage as compared to other sites ( P = 0.04). Surgery was performed with curative intent in 72%, while 2% had palliative surgery for symptom control. Of the remaining patients who did not undergo surgery, four had palliative chemotherapy and/or radiotherapy. Median disease‐free survival was 13 months (1–179 months). There was a significantly longer time to locoregional recurrence in head and neck MM (16 months) compared to other sites (11 months) ( P = 0.03). The 2‐year overall survival was also significantly higher in head and neck MM ( P = 0.003). Conclusion: MM of the head and neck is diagnosed at an earlier stage and associated with a longer time to locoregional recurrence. Surgical resection is the mainstay of treatment and may offer long‐term survival benefit in selected patients.